Reinterpretasi Konsep Maṣlaḥah Dalam Mazhab Mālikī dan Relevansinya Terhadap Problematika Hukum Islam Kontemporer: A Reinterpretation of the Concept of Maṣlaḥah in the Mālikī School and Its Relevance to Contemporary Issues in Islamic Law - Suandi Suandi; Jumarni Dalle; Nurchaliq Majid; Inda Sari Palinrungi; Rasdiana; Kasmanita (Sekolah Tinggi Agama Islam Negeri Majene, 2026)
This article examines the reinterpretation of maṣlaḥah in the Mālikī School of Law and its relevance to contemporary Islamic legal issues in a global context. It departs from the tension between textual-normative reasoning and the increasing need to contextualize Islamic law. The study argues that maṣlaḥah is not merely a utilitarian instrument, but a methodological principle rooted in the Mālikī uṣūl al-fiqh tradition and oriented toward the realization of maqāṣid al-sharīʿah. Historically, maṣlaḥah developed through three phases. The first was a practical phase grounded in the social reality of Madinah and the tradition of ʿamal ahl al-Madīnah. The second was a systematic phase in which maṣlaḥah was integrated with the maqāṣid framework, especially in medieval legal thought. The third was a contemporary phase marked by the demand for contextual reinterpretation. Using library research and a conceptual-historical approach, this article analyzes the thought of Mālikī scholars, especially Mālik ibn Anas and al-Shāṭibī, and its development in contemporary scholarship. This study finds that many previous works discuss maṣlaḥah in a normative, abstract, and cross-madhhab manner, which obscures the distinctive epistemological character of the Mālikī tradition. The findings show that reinterpretating Mālikī maṣlaḥah through maqāṣid al-sharīʿah provides a controlled evaluative framework for addressing global issues, such as human rights, social justice, bioethics, public governance, and digital technology ethics. This article contributes a systematic and applicable framework for moderate, contextual, and substantively just Islamic legal ijtihad, while preserving legal continuity, methodological accountability, and the normative authority of Islamic law in modern societies.